Existencia de autonomía fiscal de los departamentos colombianos en la descentralización territorial en la normativa vigente desde la Constitución política de 1991 (2022)
The fiscal autonomy of the territorially decentralized departments in Colombia has been the subject of debate due to the serious crisis that was evidenced by the Covid-19 pandemic, coupled with this, given the difficult situation that territorial entities are going through, for that matter. From the study, the departments when making decisions that promote the development and protection of the associates by providing the protection of the essential purposes of the State, it was evidenced that the fiscal autonomy of the departments was scarce when meeting the health needs and promoting the development of the departments and with this, the question arose of being able to establish whether or not there was fiscal autonomy for the departments within the regulations that were in force, this in order to investigate and elucidate whether or not such fiscal autonomy exists and whether it satisfies the purposes essential of the State. Reason why, in this research work, it will be demonstrated that, if there is fiscal autonomy for territorial entities such as departments, but that there are regulatory gaps in which they provide little fiscal autonomy for the departments to define the limitations on the departments by the national political Constitution and lax regulations that give the departments a free hand to develop autonomy with greater fiscal freedom or greater legal regulation to limit dependence on the State and thus meet the needs of the more immediate the essential purposes of the State established for the departments.